Colored passive daytime radiative cooling coatings based on dielectric and plasmonic spheres. (5th November 2022) - Chen, Meijie; Pang, Dan; Yan, Hongjie
Highlights: A simple method is designed to create bilayer-colored PDRC coatings. R ¯ s o l a r and ε ¯ L W I R of the white PDRC coating can be 0.94 and 0.93 at 300 μm. R ¯ s o l a r of colored coatings can be 0.859 (with Au layer) and 0.822 (with Ag layer). Colored coatings show better PDRC performance than commercial white coatings. Abstract: Passive daytime radiative cooling (PDRC) is a promising alternative to current compression-based cooling systems, which can directly radiate energy into outer space with a high thermal emittance ( ε ¯ L W I R ) in the long-wavelength infrared atmospheric transmission window. It's critical to enhance solar reflectance ( R ¯ s o l a r ) to avoid solar heating in the daytime. Meanwhile, the super-white color is generally not desirable due to aesthetics. Here, we design a bilayer coating that simultaneously achieves colored PDRC by using the optimized SiO2 microspheres for PDRC in the underlayer and intrinsic narrow absorption of plasmonic nanospheres for color in the thin top layer. Experimental results indicate that R ¯ s o l a r and ε ¯ L W I R of the white SiO2 coating can be optimized as: R ¯ s o l a r = 0.942 and ε ¯ L W I R  = 0.931. Furthermore, R ¯ s o l a r of the colored PDRC coating with the Au layer would weaken slightly to be 0.859, ε ¯ L W I R still maintains as 0.933. Note that both of them are higher than that of the commercial coatings ( R ¯ s o l a r  = 0.836, ε ¯ L W I R = 0.925). Under the direct sunlight of ∼881 W/m 2, the white PDRC coating achieves a temperature decrease of up to 10.9 °C, which is 7.5 °C (with Au layer) and 5.1 °C (with an Ag layer) for colored PDRC coatings. In addition, the PDRC coating has great storage stability, excellent water repellency, substrate adaptability, and fire resistance, allowing it suitable and practical for large-scale commercial and sustainability applications.